The relative importance of species richness and functional diversity for ecosystem functions performed by dung beetles (Coleoptera: Scarabaeidae) in South Africa. - Simba, Lavhelesani Dembe (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDConsEcol)--Stellenbosch University, 2020.